2016
DOI: 10.21273/hortsci11018-16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dry-injection Cultivation to Maintain Soil Physical Properties for an Ultradwarf Bermudagrass Putting Green

Abstract: Traditional hollow-tine (HT) aerification programs can cause substantial damage to the putting green surface resulting in prolonged recovery. Despite the growing interest in new and alternative aerification technology, there is a lack of information in the literature comparing new or alternative technology with traditional methods on ultradwarf bermudagrass [Cynodon dactylon (L.) Pers. × C. transvaalensis (Burtt-Davy)] putting greens. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 15 publications
1
30
1
Order By: Relevance
“…It should be noted that the tine spacing for HTC was much closer than SIC which resulted in approximately seven and five holes within the inner ring of the infiltrometer for HTC and SIC, respectively. Craft et al (2016) also reported that SIC applied five times per year did not improve the infiltration rate compared to nontreated control. This lack of effect is possibly due to a relatively small area of impact and no alleviation of surface compaction.…”
Section: Infiltration Ratementioning
confidence: 94%
See 4 more Smart Citations
“…It should be noted that the tine spacing for HTC was much closer than SIC which resulted in approximately seven and five holes within the inner ring of the infiltrometer for HTC and SIC, respectively. Craft et al (2016) also reported that SIC applied five times per year did not improve the infiltration rate compared to nontreated control. This lack of effect is possibly due to a relatively small area of impact and no alleviation of surface compaction.…”
Section: Infiltration Ratementioning
confidence: 94%
“…The process was repeated until two consecutive readings were the same. Surface firmness was measured using a handheld firmness meter (Field Scout TruFirm; Spectrum Technologies) which records the penetration depth of a falling plunger as it hits a surface (Craft et al, 2016;Dickson et al, 2017). Firmness was measured following the single drop of the plunger on nine points across a grid and averaged within each plot for subsequent analyses.…”
Section: Crop Sciencementioning
confidence: 99%
See 3 more Smart Citations